Earthquakes initiation and thermal shear instability in the Hindu Kush intermediate depth nest (2016)
Intermediate depth earthquakes often occur along subducting lithosphere, but despite their ubiquity the physical mechanism responsible for promoting brittle or brittle?like failure is not well constrained. Large concentrations of intermediate depth earthquakes have been found to be related to slab break?off, slab drip, and slab tears. The intermediate depth Hindu Kush nest is one of the most seismically active regions in the world and shows the correlation of a weak region associated with ongoing slab detachment process. Here we study relocated seismicity in the nest to constraint the geometry of the shear zone at the top of the detached slab. The analysis of the rupture process of the Mw 7.5 Afghanistan 2015 earthquake and other several well?recorded events over the past 25?years shows an initially slow, highly dissipative rupture, followed by a dramatic dynamic frictional stress reduction and corresponding large energy radiation. These properties are typical of thermal driven rupture processes. We infer that thermal shear instabilities are a leading mechanism for the generation of intermediated?depth earthquakes especially in presence of weak zone subjected to large strain accumulation, due to ongoing detachment process.